Geotechnology applied in the analysis of the impacts on the land use and land cover caused by the construction of a hydroelectric plant - Ziembowicz, Matheus Morais; Marchesan, Juliana; Baratto, Jakeline; Alba, Elisiane; Silva, Robson Righi da; Pereira, Rudiney Soares (Ciência e Natura, 2018)
The objective of the research was to verify the changes in land use and land cover in the area of influence of the São José Hydroelectric Plant, Rio Grande do Sul state, between the years 2007 and 2017, using images of medium spatial resolution. For this, was used images of the TM/Landsat 5 sensor were used for the year 2007 and images the OLI/Landsat 8 sensor for 2017. Classification was supervised using the Battacharyya classifier, with the creation of six land use and land cover classes: Agriculture, Water, Urban Area, Field, Native Forest and Exposed Soil. The image processing and analysis were performed in the SPRING software version 5.4.2. With the results, it was noticed that the most expressive classes of use and land cover in the study area included Agriculture, Field and Exposed Soil, however, they reduced their occupation areas from 75% to 68% of the study area in 2017, while the native forest increased its area comprising 26% in 2017. Thus, it was concluded that with the construction of the São José hydroelectric plant there were environmental impacts in which areas were suppressed due to flooding, however, native forest areas increased after the installation hydroelectric plant.